KONTRIBUSI KECERDASAN INTRAPERSONAL TERHADAP KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Dyah Savitri; Dianti, Puspa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between intrapersonal intelligence and learning independence in Pancasila Education among seventh-grade students at SMP Negeri 11 Palembang. The research employed a quantitative correlational design involving 76 students selected through purposive sampling. Data were collected using intrapersonal intelligence and learning independence questionnaires supported by classroom observation data. The results show that students’ intrapersonal intelligence is predominantly in the moderate category, while learning independence is classified in the high category. Pearson Product Moment correlation analysis indicates a very strong positive relationship between intrapersonal intelligence and learning independence, with a correlation coefficient of r = 0.983 and a significance value of p < 0.001. These findings indicate that strengthening students’ intrapersonal intelligence may contribute to the development of independent learning in Pancasila Education.